Development of Qibla Direction Determinant Using Sun Shadow - Syazwan Faid, Muhamad; Muhammad Syaoqi Nahwandi,; Mohd Saiful Anwar Bin Mohd Nawawi,; Nurulhuda Binti Ahmad Zaki,; Mohd Saadon, Mohd Hafiz (Online Journal of Research in Islamic Studies, 2022)
The determinant of direction of the Kaaba or Qibla is important to Muslim as it is an obligation for Muslim prayer. A study shows a degree of azimuth displacement will result to a 138.3 km difference, meaning the direction is facing 138.3 km away from Kaaba. Thus, to ensure that the direction is facing the Kaaba, the accuracy of the direction is essential. Therefore, this study aimed to discuss the method of determining the Qibla direction using Sun Shadow, that can determine the times of Sun shadow facing the Qibla direction for various location at various time. The method is published in the form of Microsoft Excel to demonstrate how the formulation is practiced. The method is tested on 5 locations, representing various direction from Mecca, and Equator of the earth, on solar Solstice and Equinox. The method is computed using Jean Meeus Astronomical Algorithm. The result show that the method capable of determining direction of the Qibla at any given location and times with the accuracy error of 30 arc second. The accuracy of the method is better phone compass which has average error of 20 minute. The method will help Muslim in authenticating their Qibla direction by using Sun shadow.